ETHNOMATHEMATICS IN THE FORM OF MARKET SNACKS IN JARGARIA MARKET DOBO - Purba, Pratiwi (Program Studi Pendidikan Matematika (Kampus Kab. Maluku Barat Daya) Universitas Pattimura, 2024)
Dobo City, a small settlement in the Aru Islands, which is rich in traditional heritage, establishes traditional foods such as market snacks as an integral part of traditional processions. The purpose of this study is to identify the various geometric shapes found in various market snacks and their relation to mathematics. The ethnomathematics approach was used in the research method to analyse the various shapes of market snacks based on the properties of flat and spatial shapes contained in the School curriculum. This research is descriptive qualitative, with data collection conducted through literature review, field observations, and interviews with various related parties. There are various mathematical geometric elements identified in this study, such as flat shapes in the form of triangles and circles, as well as spatial shapes such as blocks, balls, and tubes. The results of this study are expected to contribute to the development of contextual learning, especially in the application of mathematical concepts in the context of everyday life.